The doll funeral : a novel - Hamer, Kate (Melville House, 2017)
""[Evokes] both Jeanette Winterson and Ian McEwan. an elegiac and uplifting novel about the indissoluble bonds between mothers and daughters, and a reminder of how the imagination can set you free." -- The Guardian. On Ruby's thirteenth birthday, a wish she didn't even know she had suddenly comes true: the couple who raised her aren't her parents at all. Her real mother and father are out there somewhere, and Ruby becomes determined to find them. Venturing into the forest with nothing but a suitcase and the company of her only true friend--the imaginary Shadow Boy--Ruby discovers a group of siblings who live alone in the woods. The children take her in, and while they offer the closest Ruby's ever had to a family, Ruby begins to suspect that they might need her even more than she needs them. And it's not always clear what's real and what's not--or who's trying to help her and who might be a threat. Told from shifting timelines, and the alternating perspectives of teenage Ruby; her mother, Anna; and even the Shadow Boy, The Doll Funeral is a dazzling follow-up to Kate Hamer's breakout debut, The Girl in the Red Coat, and a gripping, exquisitely mysterious novel about the connections that remain after a family has been broken apart"--